2011
DOI: 10.4315/0362-028x.jfp-10-486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Resistance of Benzalkonium Chloride–Adapted and –Nonadapted Biofilms of Listeria monocytogenes to Modified Atmosphere Packaging and Nisin Once Transferred to Mussels

Abstract: Benzalkonium chloride-adapted and -nonadapted Listeria monocytogenes biofilm cells were transferred by contact to cooked or live mussels and packed in rich CO(2) and O(2), respectively. The viabilities of transferred cells during storage of these packed samples at 2.5 °C were compared. In addition, in cooked mussels the combined effect of CO(2) and nisin against the survival of L. monocytogenes was also studied by using a first-order factorial design. The results obtained demonstrated that biofilms formed by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In fact, in previous studies BAC-adapted cells were obtained after days or even weeks of culture (Aase et al, 2000;To et al, 2002;Romanova et al, 2006) as it can be observed in the Table 4. Moreover, adapted cells obtained with the proposed method in 2008 had been used during years in subsequent studies (Saá Ibusquiza et al, 2011a, 2011b, 2012 and no reversion in the adaptation to BAC was observed.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, in previous studies BAC-adapted cells were obtained after days or even weeks of culture (Aase et al, 2000;To et al, 2002;Romanova et al, 2006) as it can be observed in the Table 4. Moreover, adapted cells obtained with the proposed method in 2008 had been used during years in subsequent studies (Saá Ibusquiza et al, 2011a, 2011b, 2012 and no reversion in the adaptation to BAC was observed.…”
Section: Discussionmentioning
confidence: 93%
“…The determination of pharmaceutics and biocides in biota, including the analysis of invertebrates, plankton, fish, human tissues and fluids, birds, and marine mammals, is importance for assessing the risk for human health and environmental damage [ 38 , 39 ], as well as determining the potential ecological risk index [ 38 , 39 , 40 ]. The biomonitoring includes saltwater and freshwater mussels [ 1 , 41 , 42 , 43 ]. These biological species filter large quantities of water, thus accumulating both organic and inorganic pollutants from water or suspended matter at elevated levels.…”
Section: Introductionmentioning
confidence: 99%